Economic impact of HIV/AIDS on households - Falleiro, Savio P. (SAGE Publications India Pvt Ltd, 2014)
This book addresses an issue of international, national and local importance-HIV/AIDS-an issue where the predominant attention is on the humanitarian and developmental catastrophe that it is accused of leading to, particularly in the developing world. The book, based on a first-of-its-kind study conducted in Goa (India), will be of great assistance to researchers as well as policy makers. It will assist policy makers in assessing the (in)adequacy of the measures taken by the government, NGOs and donors in combating the scourge of HIV/AIDS.